Antifungal garcinia acid esters from the fruits of garcinia atroviridis - Mackeen, Mukram M.; Ali, Abdul Manaf; Lajis, Nordin; Kawazu, Kazuyoshi; Kikuzaki, Hiroe; Nakatani, Nobuji (De Gruyter, 2002)
Two new garcinia acid derivatives, 2-(butoxycarbonylmethyl)-3-butoxycarbonyl-2-hydroxy3-propanolide and 1′,1″-dibutyl methyl hydroxycitrate, were isolated from the fruits of Garcinia atroviridis guided by TLC bioautography against the fungus Cladosporium herbarum. The structures of these compounds were established by spectral analysis. The former compound represents a unique β-lactone structure and the latter compound is most likely an artefact of garcinia acid (= hydroxycitric acid). Both compounds showed selective antifungal activity comparable to that of cycloheximide (MID: 0.5 μg/spot) only against C. herbarum at the MIDs of 0.4 and 0.8 μg/spot but were inactive against bacteria (Bacillus subtilis, methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli), other fungi (Alternaria sp., Fusarium moniliforme and Aspergillus ochraceous) including the yeast Candida albicans.